Analysis of Factors that Influence the Investment Interest of Islamic Economics Students at State University of Surabaya - Masyhuri, Tsabitah Fathin; Munir, Maryam Bte Badrul (PT FORMOSA CENDEKIA GLOBAL, 2024)
The rise of the younger generation's interest in investing in the capital market is increasingly evident, this phenomenon can be shown by the increase in interest that is inseparable from the role of social media. About 75% of the young generation began to show interest in investing. The rapid development of stocks, especially Islamic stocks, is the beginning of the assumption that the context of usury in savings or investment interest is the same as gambling. That way, this study aims to determine whether there is an effect of investment motivation and expected return on the investment interest of State University of Surabaya Islamic Economics students Class of 2020 - 2022. The research method used is descriptive quantitative research with SPSS version 23 analysis. The sample used was 96 respondents through an online questionnaire with certain qualifications. The findings of this study state that investment motivation and expected return have a significant effect on student investment interest. The results of the study based on the f test show that investment motivation and expected return simultaneously affect student investment interest.